Sculpture with a Torch. - Rood, John (University of Minnesota Press, 1968)
John Rood, a sculpture and former professor of art at the University of Minnesota, provides in this book a practical, how-to-do-it discussion of the technique of welded metal sculpture. In addition to serving as an instruction manual for students and arti.